The economics of water efficiency: a review of theories, measurement issues and integrated models - Billi A.; Canitano G.; Quarto A. (Water use efficiency and water productivity: WASAMED project, 2007)
The present paper focuses on the economics of water efficiency, in its theoretical foundations, statistical developments, and interactions with hydrology. After defining the various concepts of water use efficiency and the main techniques for its valuation, the paper presents the main indicators that can be used for measuring economic efficiency in water use and the basic characteristics of an integrated hydrologic-economic water accounting system. Finally, the main issues at stake in integrating different perspectives into a comprehensive model are presented, in order to give suggestions on how to design appropriate policies for water resources planning and management.
4. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2005/09/30-2005/10/04, Amman (Jordan)